Floristic composition and diversity of indigenous wild food resources in northwestern Cagayan, Philippines - SHELLA B. CACATIAN; JOHN LESTER T. TABIAN (Society for Indonesian Biodiversity, 2023)
Abstract. Cacatian SB, Tabian JLT. 2023. Floristic composition and diversity of indigenous wild food resources in Northwestern Cagayan, Philippines. Biodiversitas 24: 2324-2333. The indigenous knowledge of the floristic composition and the species diversity of wild food resources are primary indicators for wildlife management and conservation. The present study surveyed the ethnobotany of the indigenous wild plants, the possible environmental threats, and the traditional conservation practices of the rural people in the remote barangays of Sta. Praxedes, Claveria, Sanchez Mira, Pamplona and Abulug in Northwestern Cagayan, Philippines. The study employed a field-based cross-sectional design. Forty-eight wild plant species belonging to 42 families, mainly Moraceae, Solanaceae, Amaranthaceae and Cucurbitaceae, were harvested for food by the rural communities in the study areas. Among the identified species, trees and perennials were reported to be the most dominant. The most significant proportion grows in the lowland. Fruits and leaves are the most harvested plant parts consumed raw and or cooked. The phenological calendar was developed in relation to the specific months when the edible plant parts are available for harvest within the study sites. Agricultural land expansion or development, overexploitation of wildlife, and excessive rainfall are the greatest threats to plant diversity. Considering the importance of these food resources, the locals primarily keep and protect them from potential threats through harvesting and use of selected plants or plant parts, collecting firewood from dead and fallen trees, and domesticating and cultivating indigenous wild plants.